Vitamin D status and tic disorder: a systematic review and meta-analysis of observational studies - Lin Xiaoxia; Jiang Jilong; Chen Xianrui; Chen Yanhui (Frontiers Media S.A., 2023)
ObjectiveTic disorders (TD) are a common neurodevelopmental disorder, it can be divided into transient tic disorder (TTD), chronic motor or vocal tic disorder (CTD), and Tourette syndrome (TS). Our research is to evaluate the clinical relationship between tic disorders and vitamin D level in children.MethodsOnline databases, including CNKI, Wanfang, VIP, Cochrane Library, PubMed and Embase digital knowledge service platform, were checked up to June 2022 for relevant observational studies published in Chinese and English. A random-effects model was incorporated to summarize the study results. The RevMan5.3 software was used for meta-analysis.ResultsOut of 132 retrieved articles, 13 observational studies were eligible for inclusion in the systematic review and meta-analysis, comparing serum Vitamin D levels between children with TD and HC (healthy controls), including different subtypes of TD (TTD, CTD and TS). The results showed that the serum vitamin D levels in the TD group were lower than those in the HC group (MD = −6.64, 95% CI: −9.36 to −3.93, P < 0.001, Heterogeneity test: P < 0.001, I2 = 94%). There were no statistically significant differences in serum vitamin D levels between the TTD group and the CTD group (MD = 3.84, 95% CI: −0.59 to 8.26, P = 0.09, Heterogeneity test: P < 0.001, I2 = 90%), or between the CTD group and the TS group (MD = 1.06, 95% CI: −0.04 to 2.16, P = 0.0, Heterogeneity test: P = 0.54, I2 = 0%). However, there was a statistically significant difference in serum vitamin D levels between the TTD group and the TS group (MD = 5.24, 95% CI: 0.68-9.80, P = 0.02, Heterogeneity test: P < 0.001, I2 = 92%). The study also found a statistically significant difference in the ratio of male children between the TD group and the HC group (OR = 1.48, 95% CI: 1.07-2.03, P = 0.02, Heterogeneity test: P < 0.001, I2 = 74%), but no statistically significant difference in the age of children between the TD group and the HC group (OR = 0.46, 95% CI: −0.33 to 1.24, P = 0.25, Heterogeneity test: P < 0.001, I2 = 96%).ConclusionsOur meta-analysis showed that the vitamin D level of children with TD was lower than that of healthy children. However, there was no difference between the subgroup. Due to the limitations of included studies in research design and diagnostic criteria, large samples, multi-center and high-quality studies are still needed for further analysis and confirmation.